2019
DOI: 10.1515/jbcpp-2019-0349
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing angiogenesis vasa vasorum through Lp-PLA2 and H2O2 inhibition by PSP from Ganoderma lucidum in atherosclerosis: in vivo diabetes mellitus type 2

Abstract: BackgroundType 2 diabetes mellitus (T2DM) is a major risk factor of atherosclerosis. Hyperglycemia in T2DM causes advanced formation of glycation end products (AGE) which leads to oxidative stress and chronic inflammation. Oxidative stress occurs due to increased levels of reactive oxygen species (ROS) such as H2O2. On the other hand, lipoprotein-associated phospholipase (Lp-PLA2) has pro-inflammatory effects, which cause instability of atherosclerosis plaques. This condition causes hypoxemic cells to stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Cd found on a normal blood test is <5.0 ng / mL, with most results in the range 0.5 to 2.0 ng / mL (19) . Lack of nitric oxide (NO) will cause decreased homeostasis of blood vessels which will lead to endothelial dysfunction (20) . Impaired endothelial function will cause oxidation stress and will later become a factor in the occurrence of cardiovascular disease (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Cd found on a normal blood test is <5.0 ng / mL, with most results in the range 0.5 to 2.0 ng / mL (19) . Lack of nitric oxide (NO) will cause decreased homeostasis of blood vessels which will lead to endothelial dysfunction (20) . Impaired endothelial function will cause oxidation stress and will later become a factor in the occurrence of cardiovascular disease (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, another polysaccharide peptide (PsP) extracted from G. lucidum had an active substance in the form of β‐glucan. Further studies confirmed PsP may be an effective antioxidant to delay atherosclerosis in atherosclerotic rats and in patients with high risk and stable angina via inhibiting oxidative stress, endothelial injury, and inflammation (Sargowo et al, 2018; Wihastuti et al, 2020; Wihastuti & Heriansyah, 2017). Li, Tang, et al (2021) demonstrated that G. lucidum polysaccharide (GLPs) could attenuate early aortic atherosclerotic plaque in HFD japanese big‐ear white rabbits.…”
Section: Plant Polysaccharidesmentioning
confidence: 97%
“…G. lucidum mycelia mediated the leukocyte metabolism and oxidative stress in DM rats [302]. The ROS and chronic inflammation induced by advanced glycation end products (AGE) are associated with hyperglycemia and finally result in vasa vasorum angiogenesis, but this pathologic process can be interfered with by polysaccharide peptide (PSP) isolated from G. lucidum [303]. PSP in G.…”
Section: The Regulation Of G Lucidum In Diabetes Mellitusmentioning
confidence: 99%